Análise retrospectiva e tendências do serviço de inspeção do estado de São Paulo - Garnica, Maria Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Considering the importance of sanitary inspection of animal products , the constitutional responsibility delegated to the State and the frequent economic and legislative changes in this sector , aimed to the realization of a diagnosis of the situation Inspection Service Sao Paulo - SISP , proposing is conducting a retrospective analysis of his early period to the present day and , while exploring possible trends that in order to assist in planning future actions and demands of this important state of the federation service. The survey was developed through an analytical process of a set of documents belonging to sanitary inspection obtained in Inspection Center for Animal Products - CIPOA and managerial human resources unit of the Coordination of Agricultural Defense - CDA . The results showed that the economic policies of decentralization suffered by the State of São Paulo in the 90s and normative techniques for the production of published in the federal and state levels in the corresponding period of research directly influenced foods in the design and sizing of the service process state inspection. The surveys of technical and health challenges, like the index of 1.36% of cysticercosis' prevalence in 2011 in cattle slaughtered in state stores and analyzes Drip Test within the legal standard in frozen chicken carcasses originating from state industries, show that may have faults in the capture of official data despite the satisfactory numbers. New legal requirements such as Good Manufacturing Practices are not properly implemented in registered establishments indicates the need for more effective action by the tax inspection service with specific training to analyze and check the manual for your staff . The results showed a need for an update on legislation specifies the service because the current state technical regulations have become outdated before preconizações approaches and the food industry . For a perceptive next ...

Considerando a importância da inspeção sanitária dos produtos de origem animal, a responsabilidade constitucional delegada ao Estado e as freqüentes mudanças econômicas e legislativas deste setor, objetivou-se a realização de um diagnóstico de situação do Serviço de Inspeção de São Paulo – SISP, propondo-se a realização de uma análise retrospectiva do seu período inicial até os dias atuais e, ao mesmo tempo, explorando possíveis tendências desse serviço de modo a auxiliar no planejamento de ações e demandas futuras desse importante estado da federação. A pesquisa foi desenvolvida através de um processo analítico de um conjunto de documentos pertencentes à inspeção sanitária obtidos no Centro de Inspeção de Produtos de Origem Animal - CIPOA e na unidade gerencial de recursos humanos da Coordenadoria de Defesa Agropecuária – CDA. Os resultados evidenciaram que as políticas de descentralização econômica sofridas pelo Estado de São Paulo na década de 90 e as normativas técnicas relativas à produção de alimentos publicadas nas esferas federais e estaduais no período correspondente à pesquisa influenciaram diretamente no processo de estruturação e dimensionamentos do serviço de inspeção estadual. Os levantamentos dos desafios técnicos e sanitários, como o índice de 1,36% de prevalência de cisticercose no ano de 2011 em bovinos abatidos nos estabelecimentos estaduais e as análises de Drip Test dentro do padrão legal em carcaças congeladas de frango oriundas das indústrias estaduais, demonstram que, apesar de apresentar números satisfatórios, podem significar também que há existência de falhas na capitação de dados oficiais. Novas determinações legais como as Boas Práticas de Fabricação não se encontram devidamente implantadas nos estabelecimentos registrados sugerindo a necessidade de mais efetiva ação fiscal por parte do serviço de inspeção, com treinamentos ...
Keywords: Fabricas - Higiene; Alimentos - Adulteração e inspeção; Produtos animais; Qualidade dos produtos; Controle de qualidade; São Paulo (Estado); Inspection